Aqiqah Jaya Bersaudara APLIKASI SUSUNAN RANSUM TERNAK KAMBING BERSAMA MITRA USAHA AQIQAH JAYA BERSAUDARA KECAMATAN BATANGTORU, TAPANULI SELATAN: Ransum Ternak Kambing - Angelia Harahap; Rikardo Silaban; Novita Aswan; Toga Mahaji; Dina Syahfitri (Journal of Community Service (JCOS), 2023)
Successful community economic development has a positive influence on increasing people's income and purchasing power. One very strategic business to increase the income of farmers in Batangtoru sub-district, South Tapanuli is the goat meat aqiqah business. The obstacle encountered during the field survey of livestock business partners was that the aqiqah business process was not yet optimal in terms of nutritional management of animal feed and marketing of aqiqah business products. This is due to the lack of knowledge of breeders in proper production and marketing. The aim to be achieved in this service activity is to increase the knowledge of breeders in implementing and compiling quality goat rations from cheap and easily available ingredients and to help increase the income and welfare of the breeders themselves. This service activity began with a focus group discussion (FGD) system approach, Participal Rural Appraisal (PRA) and continued with counseling, piloting and direct application by breeders. The participation and motivation of groups of farmer-breeders in taking part in a series of community service activities is very high. Because so far there has never been any training related to technical aspects and nutritional management from the application of omega 3.6 sources together with Moringa oleifera supplemented with vitamin E for goat meat from the Aqiqah Jaya Brothers Batangtoru business, South Tapanuli.